Mediasi Pemberdayaan Psikologis pada Pengaruh Kepemimpinan Pemberdayaan terhadap Berbagi Pengetahuan - Handayani, Ririn; Fawzi, Rizky; Bastian, Adolf (CV. ITTC INDONESIA, 2024)
This study uses a quantitative method with a descriptive and explanatory survey approach. The study was conducted at the Kampar Regency Land Office, with the aim of testing the mediation effect of empowerment leadership on the relationship between psychological empowerment and knowledge sharing. The population of this study consisted of all employees of the Kampar Regency Land Office, with a total of 144 people. Based on this population size, according to the Krejcie and Morgan (1970) table, the sample size for this study was 103 people. The sampling method used in this study was Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that (a). empowerment leadership has a significant positive effect on knowledge sharing; (b). empowerment leadership has a significant positive effect on psychological empowerment; (c). psychological empowerment has a significant positive effect on knowledge sharing; (d). psychological empowerment mediates the effect of empowerment leadership on knowledge sharing. This study uses a quantitative method with a descriptive and explanatory survey approach. The study was conducted at the Kampar Regency Land Office, with the aim of testing the mediation effect of empowerment leadership on the relationship between psychological empowerment and knowledge sharing. The population of this study consisted of all employees of the Kampar Regency Land Office, with a total of 144 people. Based on this population size, according to the Krejcie and Morgan (1970) table, the sample size for this study was 103 people. The sampling method used in this study was Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that (a). empowerment leadership has a significant positive effect on knowledge sharing; (b). empowerment leadership has a significant positive effect on psychological empowerment; (c). psychological empowerment has a significant positive effect on knowledge sharing; (d). psychological empowerment mediates the effect of empowerment leadership on knowledge sharing.